(untitled) (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2026)
Introduction. Occupational exoskeletons are wearable devices designed to reduce the biomechanical load on the joints most stressed during physically demanding and/or highly repetitive work tasks. The reduction of joint stress induced by the use of such devices could contribute to a decrease in the incidence of work-related musculoskeletal disorders.1 However, there is currently insufficient longitudinal scientific evidence available to demonstrate a direct causal relationship between exoskeleton use and a decrease in the incidence of such pathologies.2 Objectives. The objective is to provide an overview of the occupational exoskeletons currently available in the state of the art, with a specific focus on the most relevant technical aspects and the experimental process used to evaluate their effectiveness. Taking the development of a passive upper limb exoskeleton as an example, the experimental path will be discussed, and in particular: - The main results of laboratory tests conducted under structured conditions;3 - The main results of experimental activities carried out with experienced operators in specific work contexts;4,5 - The main results of the first longitudinal study aimed at evaluating the long-term effects, including any adverse effects.6 Methods. The methods used in the experimental activities include both instrumental measurements and perceptual evaluations.1 Specifically, muscle activity is generally monitored using surface electromyography to determine any reduction in muscle effort associated with the use of the exoskeleton during the execution of specific motor tasks. Simultaneously, the use of questionnaires dedicated to assessing perceived effort, comfort, usability, and acceptability allows for the acquisition of information about users’ subjective perception of the technology. Finally, physiatric clinical assessments can support the characterization of long-term effects on the musculoskeletal system. Results and Conclusions. The currently available scientific literature on occupational exoskeletons consistently highlights the ability of these devices to significantly reduce joint load during repetitive and high-intensity work activities. However, different design choices (such as adopting a rigid or soft architecture, or the type of actuation) can lead to substantial variations in muscle and joint strain levels. Numerous studies conducted in real-world application settings have reported positive evidence in terms of functional effectiveness. Nevertheless, evaluating effectiveness is just one component of the large-scale implementation process. Effective adoption of such technologies requires an organic approach that includes the involvement of multiple stakeholders, as well as the active participation of end-users.7